Microsoft® Windows® Registry Guide, 2nd Edition - Honeycutt, Jerry (Microsoft Press, 2005)
Get the in-depth information you need to modify-and seamlessly manage-the Windows registry. Written for IT professionals and power users, this vital resource reveals little-known registry techniques, tricks, tips, and secrets to make your job easier. Understand the inner workings of the Windows operating system-and use the registry to get Windows Server 2003 and Windows XP to run the way you want, on a single desktop or across the network. You'll learn how to pinpoint registry settings and script registry changes, deal with registry permissions, use Windows Installer, and map Tweak UI settings. Also, find best practices for how to back up, restore, and maintain registry settings with confidence. The CD includes 100+ registry files for customizing operating system appearance and behavior, and the complete eBook. You'll learn how to: - Apply best practices to back up, restore, manage, and modify the registry - Customize group and system policies to manage multiple PCs andusers remotely - Track down registry settings and script changes - Optimize server services, including network connections and authentication - Deploy user profiles and Microsoft Office program settings - Configure security services, including Windows Firewall, templates, and service pack features - Troubleshoot the registry-resolving common problems and corruption issues Visit the catalog page for Microsoft® Windows® Registry Guide, 2nd EditionVisit the errata page for Microsoft® Windows® Registry Guide, 2nd EditionDownload the supplemental electronic content for Microsoft® Windows® Registry Guide, 2nd Edition